Chemical constituents and antihistamine activity of Bixa orellana leaf extract - Yong Yoke Keong; Zakaria Zainul Amiruddin; Kadir Arifah Abdul; Somchit Muhammad Nazrul; Ee Cheng Lian Gwendoline; Ahmad Zuraini (BMC, 2013)
Abstract Background Bixa orellana L. has been traditionally used in Central and South America to treat a number of ailments, including internal inflammation, and in other tropical countries like Malaysia as treatment for gastric ulcers and stomach discomfort. The current study aimed to determine the major chemical constituents of the aqueous extract of B. orellana (AEBO) and to evaluate the antihistamine activity of AEBO during acute inflammation induced in rats. Methods Acute inflammation was produced by subplantar injection of 0.1 mL of 0.1% histamine into the right hind paw of each rat in the control and treatment groups. The degree of edema was measured before injection and at the time points of 30, 60, 120, 180, 240 and 300 min after injection. Changes of peritoneal vascular permeability were studied using Evans blue dye as a detector. Vascular permeability was evaluated by the amount of dye leakage into the peritoneal cavity in rats. To evaluate the inhibitory effect of AEBO on biochemical mediators of vascular permeability, the levels of nitric oxide (NO) and vascular endothelial growth factor (VEGF) were determined in histamine-treated paw tissues. The major constituents of AEBO were determined by gas chromatography-mass spectrometry (GC-MS) analysis. Results AEBO produced a significant inhibition of histamine-induced paw edema starting at 60 min time point, with maximal percentage of inhibition (60.25%) achieved with a dose of 150 mg/kg of AEBO at 60 min time point. Up to 99% of increased peritoneal vascular permeability produced by histamine was successfully suppressed by AEBO. The expression of biochemical mediators of vascular permeability, NO and VEGF, was also found to be downregulated in the AEBO treated group. Gas chromatography-mass spectrometry (GC-MS) analysis revealed that the major constituent in AEBO was acetic acid. Conclusions The experimental findings demonstrated that the anti-inflammatory activity of AEBO was due to its inhibitory effect on vascular permeability, which was suppressed as a result of the reduced expression of biochemical mediators (NO and VEGF) in tissues. Our results contribute towards the validation of the traditional use of Bixa orellana in the treatment of inflammatory disorders.